Unregulated topical steroid use in India: From skin relief to lifethreatening complications (Indian Journal of Case Reports, 2026)
Unregulated and prolonged use of corticosteroids, both topical and oral, remains a significant public health concern in India, resulting in severe iatrogenic complications. We report a 35-year-old male who developed iatrogenic Cushing’s syndrome, steroid-induced diabetes mellitus, and pulmonary aspergilloma within an old tuberculous cavity following prolonged unsupervised use of high-potency topical steroid (likely clobetasol-based) for widespread eczema. This case highlights the complex interplay of endocrine disruption, metabolic derangements, and immunosuppression leading to opportunistic fungal colonization in structurally damaged lungs. Strict regulation of over-the-counter sales of potent corticosteroids, enhanced public awareness, and improved oversight of healthcare practices are urgently needed to prevent such avoidable morbidity.